2021
DOI: 10.37715/jp.v6i1.1904
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Harga, Lokasi, Dan Kualitas Layanan Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Mediator Pada Star Motor Carwash

Abstract: Star Motor Carwash adalah perusahaan yang bergerak dibidang jasa layanan cuci mobil dan motor yang terletak di Kota Malang. Star Motor Carwash memiliki permasalahan tentang penurunan omset pada tahun 2019 mengalami penurunan. Tujuan penelitian ini adalah untuk mengetahui pengaruh harga, lokasi, dan kualitas layanan terhadap loyalitas pelanggan dengan kepuasan pelanggan sebagai variabel mediator pada Star Motor Carwash. Penelitian ini menggunakan metode kuantitatif dengan menggunakan teknik pengambilan sampel n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
6
8
0
Order By: Relevance
“…Suhendra and Asworowati (2020) stated that customers will be loyal when the business location is easy to reach and feel satisfied with it. Harjono and Marlina (2021) also found that location has a positive and significant influence on customer satisfaction at Star Motor Carwash. Nofindri et al (2021) found that store location has a positive influence and is able to increase customer satisfaction at the Wirda Mini Marke t in Padang City.…”
Section: Store Locationmentioning
confidence: 80%
See 3 more Smart Citations
“…Suhendra and Asworowati (2020) stated that customers will be loyal when the business location is easy to reach and feel satisfied with it. Harjono and Marlina (2021) also found that location has a positive and significant influence on customer satisfaction at Star Motor Carwash. Nofindri et al (2021) found that store location has a positive influence and is able to increase customer satisfaction at the Wirda Mini Marke t in Padang City.…”
Section: Store Locationmentioning
confidence: 80%
“…Firdaus et al (2022) gained a significant influence between business location and customer loyalty through satisfaction. Harjono and Marlina (2021) also found that location has a significant effect on customer loyalty with customer satisfaction as a mediator variable in Star Motor Carwash. Nofindri et al (2021) also found the influence of location on consumer loyalty with consumer satisfaction as mediation at the Wirda Mini Market in Padang City.…”
Section: Customer Satisfactionmentioning
confidence: 81%
See 2 more Smart Citations
“…Ivanov & Usheva, (2021) defines behavior as an attitude or action as well as everything that humans do, for example activities carried out by humans in their daily lives, either working hard or with other people, exchanging opinions, either accepting opinions or rejecting them. The definition of work behavior (Hariono & Marlina, 2021) is how people in the work environment can actualize themselves through attitudes at work. Where this opinion emphasizes the attitude taken by workers to determine what people with this type will do in the workplace environment.…”
Section: Work Behaviormentioning
confidence: 99%